Elections in India: Strategic Nominations. (April 2014) - Mukhopadhyay, Bappaditya
The two major concerns in Indian electoral system are enormous spending and increased criminalisation of politics. While roughly one-third of all elected offices (state or national) have members with some criminal charges, the spending in 2009 general elections exceeded the total spends in the US general elections held a year earlier. This article links the two. We develop a theoretical model that views candidates as a strategic choice by the parties. We propose a two-dimensional contest function. In this framework we analyse the likely scenarios when a party chooses candidates with criminal records as well as how much to spend for that candidate. Our framework also analyses the role of reservations. We use records of 36, 731 candidates who contested elections at either Lok Sabha or Assembly level during the last 5 years.